Meneladani Kecerdasan/Fathonah Nabi Muhammad SAW dalam Mengarungi Kehidupan - Syukur, Agus; Puspita, Ratna (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2024)
This research is motivated by several things, including the negligence of the majority of Muslim communities in emulating the intelligence of the Prophet Muhammad in facing and solving various life problems. The Muslim community's ignorance and unwillingness to study the history of the life of the Prophet Muhammad means that they have no guidance, so they cannot face, let alone solve, the problems of their lives. This research aims to reveal the essence of intelligence/fathonah possessed by the Prophet Muhammad SAW, which is then used as a reference for the Muslim community as a basis or reference in navigating a life full of all trials and problems.What is used in this research is a qualitative method with a descriptive approach. The results of this research are that the Prophet Muhammad had the most perfect and diverse intelligence (multiple intelligences), In fact, no one can match the intelligence possessed by the Prophet Muhammad. The diversity of intelligence he possesses has been proven by his having held all professions and succeeded in carrying them out well, he has been in trade, he is a teacher who teaches, he is a preacher, he is a state leader, he is a warlord, he is a diplomat, he is a thinker, and so on. Therefore, it is appropriate for every Muslim to emulate the intelligence of the Prophet Muhammad as a basis or guide in living a life full of problems and challenges.Keywords: Intelligence, Fathonah, Prophet Muhammad SAW